Using satellite images for forest management in northeast Mexico - Ancira-Sánchez, Lucio; Treviño Garza, Eduardo Javier (Instituto de Ecología, A.C., 2015)
This work presents a methodological alternative for the generation of information used in the planning of forestry activities. A forest venue located in the south of the state of Nuevo Leon was taken as a site of research. The methodologies were based on the use of high-resolution satellite images which have been validated using the traditional materials (aerial photos) which served to describe the distribution of forest resources of the area and to make a comparison with regard to the quality of information obtained from these two materials. These materials were processed with the support of computer and specialized software from the Laboratory of Remote Sensing and Geographic Information Systems located in the Division of Forest Sciences of the UANL (Universidad Autonoma de Nuevo Leon). A comparison of the forest standing was made on the orthophoto and on the satellite image, with coverage for the area of study, finding that the one carried out on the satellite image presented sufficient quality to better identify the species composition and age structure. The use of high-resolution satellite images for the development of the forest mapping offers advantages over the orthophotos, in particular by the spectral resolution, which makes the forest standing in some cases easier, have the potential to be obtained repeatedly, can be processed digitally and obtain other variations such as vegetation indices.